Analisis Stok Pangan dalam Sistem Distribusi Penunjang Ketahanan Pangan - Mohammad Fuad Fauzul Mu’tamar (Agroindustrial Technology, University of Trunojoyo Madura, 2010)
The importance of food security in national development is an important issue amongall agrees that food security becomes a priority in national development. Distribution systemthat is effective and efficient as the prerequisite to ensure that all households can obtain food inquantity and quality sufficient over time, with reasonable prices. A difference of foodproduction capability between regions and between seasons requires accuracy in managing thedistribution system, so that food is available at all times throughout the region. Study on theanalysis of the stock in the food distribution system aimed at supporting food security system toget a description and identification of food stock of factors that affect the stock in the fooddistribution system. Ishikawa diagram, why-why analysis is used to identify, analyze and solveproblems. This diagram places the problems solved on the right, i.e. the fish head. Factorsidentified as a problem category are placed above and below the framework of the fish whichare connected with arrows. Discussion about the analysis results of the stock in the fooddistribution system in supporting food security comes to a conclusion: Stock food, especiallyrice comes from domestic production and the import of food reserves and the reserves comefrom the government and the community; factors that affect the stock in the food distributionsystem includes production facilities and distribution infrastructure, the condition of geography,logistics management and government regulations